Characterization and simulation of foreign object damage in curved and flat SiC/SiC ceramic matrix composites - Presby, Michael J.; Mansour, Rabih; Manigandan, K.; Morscher, Gregory N.; Abdi, Frank; Godines, Cody; Eftekharian, Amirhossein; Choi, Sung R. (Ceramics international, 2019)
Foreign object damage (FOD) phenomenon of flat and curved Hi Nicalon MI SiC/SiC ceramic matrix composite (CMC) was determined at ambient temperature subject to impact of 1.59 mm steel ball projectiles at a velocity of approximately 340 m/s. The differences in damage morphology between the flat and curved specimens was investigated through the use of electrical resistance (ER), micro-computed tomography (micro-CT), and optical microscopy. The experimental test data was then simulated with GENOA MS-PFA and LS-Dyna using rebound velocity/energy absorbed and damage size as a means to correlate experimental and simulation. The effect of curvature has a profound effect on the impact damage morphology, and must be accurately accounted for when designing full scale CMC components.